2019
DOI: 10.5758/vsi.2019.35.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience and Potential Advantages of AFX2 Bifurcated Endograft System: Comparative Case Series

Abstract: PurposeThe AFX2 endograft is a unibody, bifurcated stent graft that can be used to lower complications in certain patients. In this study, we retrospectively reviewed consecutive cases in which the AFX2 system was used to overcome the challenges of narrow distal aorta, as well as to reduce procedure time and contrast medium dose. Furthermore, we compared the results with matched patients treated using the Endurant II endograft system.Materials and MethodsThis was a retrospective observational study of nine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The AFX family of endografts has a unibody design, which allows some unique applications in patients with a narrow distal aorta [7,21] and in patients in whom preservation of the native aortic bifurcation is required for future treatment of peripheral vascular disease [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AFX family of endografts has a unibody design, which allows some unique applications in patients with a narrow distal aorta [7,21] and in patients in whom preservation of the native aortic bifurcation is required for future treatment of peripheral vascular disease [22].…”
Section: Discussionmentioning
confidence: 99%
“…The published literature on the performance of the AFX2 endograft is limited [5][6][7][8][9], but a recent publication by Chang et al (2021) [10] which reported a single integrated healthcare system experience of AFX and AFX2, suggested that the AFX2 endograft was associated with a high rate of adverse clinical events during follow up. The present study was designed to evaluate the outcomes derived by the AFX2 endograft in a series of patients from multiple centers in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…There are many restrictions placed by the manufacturer on the use of IBE with the Excluder main body [ 13 , 14 ], and appropriate preoperative planning in endovascular repair may yield satisfactory results. AFX2 (Endologix, Irvine, CA, USA) is a unique bifurcated unibody endograft that fits the small terminal aorta and provides a proper landing zone for the common iliac artery (CIA) [ 18 , 19 ]. We report two cases of successful endovascular repair of iliac arterial aneurysms aiming to prevent pelvic ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…The AFX endovascular aortic aneurysm system (AFX stent graft; Endologix, Irvine, CA) is a unique bifurcated endograft with an Active Seal technology (Supplementary Figure 1). 68 The Active Seal technology uses a graft material that is externally mounted and attached only at the proximal and distal ends of the stent, which allows the conformable expanded polytetrafluoroethylene (ePTFE) material to expand independently of the stent by the blood pressure (Figure 1). It can accommodate various aortic wall shapes at the proximal and distal sealing zones 7,8 and extend the proximal sealing zone.…”
Section: Introductionmentioning
confidence: 99%